KONDISI SANITASI DAN PERSONAL HYGIENE PENJAMAH MAKANAN DENGAN KEBERADAAN ESCHERICHIA COLI PADA PERALATAN MAKAN DI RUMAH MAKAN AREA BANDARA SAM RATULANGI MANADO - Irmawaty Buleno; Jasman Jasman; Suwarja Suwarja; Agnes T. Watung (POLTEKKES KEMENKES MANADO, 2018)
Cleanliness of cutlery is a very important part and affect the quality of food and beverages. The purpose of this study is to determine the relationship between sanitary conditions and personal hygiene food handlers with the presence of Escherichia Coli on eating utensils in the restaurant area of ​​Sam Ratulangi Airport Manado. This type of research is an observational analytic study with cross sectional study design. The entire population of 5 restaurants and food handlers that amounted to 25 people were used as samples, and examination of a tableware sample consisting of 4 types of cutlery ie plates, cups, spoons and forks with a total sample of eating utensils of 20 samples. Processing and analysis univariate data, 80% qualified water supply, 20% unqualified, 60% unqualified wastewater disposal, 40% qualified, cleansing equipment 40% qualified, 60% unqualified, food processing 60% qualified, 40% unqualified, personal hygiene food handler 55% unqualified, 45% qualified. Suggestion: For the managers of Angkasa Pura I and the Manado Port Health Office Class II to controlling every restaurant around Sam Ratulangi Airport in Manado, more specifically overseeing the condition of sanitation and food handlers.